(untitled) (Acta Polytechnica CTU Proceedings, 2019)
The study focuses on the influence of addition of four different biopolymers in various doses (0.1%, 0.5%, and 1%) on the physical-mechanical properties and durability of NHL 3.5 mortars prepared with constant water/binder ratio and the binder/aggregate ratio of 1 : 2 by weight. The flow table test was carried out and the specimens were tested for flexural and compressive strength at the age of 7 and 28 days. The durability coefficient for the flexural strength was calculated after 15 freezing-thawing cycles. All the admixtures have dosage-dependent slump reducing effect. The strengths were increased in comparison with mortar with no admixture, the most significantly in the case of highest dose of carrageenan and diutan gum. All biopolymers with the exception of diutan gum increased the durability coefficient with increasing dosage. Sodium salt of alginic acid has been found the most effective in the case of durability improvement.